Pendampingan Pertolongan Dasar Pada KCardiact Arrest di Desa Borisallo Kab. Gowa - Alamsyah, Alamsyah; Samsir, Samsir; Sulasri, Sulasri; Suntin, Suntin (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
An emergency condition is one of the threats that requires immediate treatment/assistance by the person who first finds the victim because the golden period for an emergency is a maximum of 10 minutes. Therefore, the community as first responders really needs to have knowledge and skills in providing assistance. The purpose of this mentoring is to increase the knowledge of teachers in Barisallo Village Kel. Parangloe Kab. Gowa. The method used is the lecture method using leaflet media and simulation using an emergency manikin and splints. This activity was carried out for 6 days. The results of the activities include the planning, implementation and evaluation stages. From the results of the service, there are still many people, especially teachers, and there are still many people who do not know how to provide first aid in emergency conditions. So from that basis, community service is about efforts to increase teacher knowledge and skills to prevent death or disability. It is hoped that health workers will be more active in conducting health education, especially in Barisallo Village, Kec. Parangloe.